Financial Inclusion and Economic Growth Nexus, Evidence from Nigeria - Emmanuel Olalekan Obademi; Christiana Adeniran (Unilag Journal of Humanities, 2019)
This study focuses on the impact of financial inclusion on economic growth in Nigeria.Primary data was gathered with the aid of questionnaires which consists of a sample sizeof 180. Two hundred and twenty (220) questionnaires were distributed amongindividuals, owners of small and medium scale enterprises within Nigeria, but onehundred and eighty were retrieved representing a response rate of 81.81%. Simple linearRegression analysis was used in testing the three hypotheses: local credit influence oneconomic growth, effect of financial inclusion on economic growth and the impact ofcommercial bank deposits on economic growth, our findings showed that there issignificant relationship between local credit and economic growth in Nigeria, It was alsofound in this study that there is significant relationship between financial inclusion andeconomic growth and that there is significant relationship between commercial bankdeposits and economic growth. Environmental factors have an impact on planning andforecasting in business management and there was a positive relationship betweenplanning and forecasting. This was reviewed through the response obtained. I, thereforerecommend that Central Bank of Nigeria should increase its vigor for pursuing financialinclusion as it not only helps with economic growth as espoused in literature, but alsoeffectuates monetary policy in Nigeria.